Pengaruh Gaya Kepemimpinan Dan Motivasi Terhadap Kinerja Guru (Study Kasus di MA Al Maarif Singosari) - Muhamad Farkhan; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine: 1. To determine the simultaneous influence of leadership style and work motivation on teacher performance at MA Al Ma'arif Singosari. 2. To determine the partial effect of leadership style and work motivation on teacher performance at MA Al Ma'arif SingosariThe method used in this study is a quantitative research method with a descriptive approach and conducted by MA Al Ma'arif Singosari with a population of 51 teachers. Data collection techniques using a questionnaire with measurements using a Likert scale. The data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, hypothesis F test, hypothesis t test and coefficient of determination test.The results of this study indicate that: 1. The results of the study prove that simultaneously leadership style and work motivation have a significant effect on teacher performance at MA Al Ma'arif Singosari. 2. The results of the study prove that partially leadership style and work motivation have a significant effect on teacher performance at MA Al Ma'arif Singosari. Keywords: leadership style, motivation and performance